Lack of association between breastfeeding duration and body mass index in children and adolescents – A Swedish cohort study - Orsolya Haahr Vad; Lisa Önnestam; Kristina Bengtsson Boström; Åsa Jolesjö; Jenny Sandegård; Tobias Andersson (PLoS ONE, 2025)
Aims The aim of the study was to investigate the association between breastfeeding duration and body mass index (BMI), overweight and obesity in children during follow-up until 16 years of age. Methods Observational cohort study of mothers and their children born 1999–2000 in a municipality in southwestern Sweden. Data were retrieved from antenatal clinics, primary care child health care centres and school health care. The study exposure was breastfeeding duration measured in months and categorised by duration < 6 months and ≥ 6 months. The study outcomes were development of BMI, and overweight and obesity according to ISO-BMI. Results The study population comprised 312 mothers and their 319 children of whom 120 were breastfed < 6 months and 199 ≥ 6 months. The overall partial or exclusive median breastfeeding duration was 6.5 months. No associations were found between breastfeeding duration in months and BMI in unadjusted (p = 0.70) and adjusted (p = 0.92) linear mixed-effects models with repeated BMI recordings at approximately 4, 7, 10, 13 and 16 years. Further, no associations were found in subgroup analyses for girls and boys. The adjusted analyses were adjusted for maternal age, smoking, BMI and parity, and for the child’s sex, gestational age at birth and birth weight. Unadjusted logistic mixed-effects models with repeated ISO-BMI classifications at approximately 4, 7, 10, 13 and 16 years showed no associations between breastfeeding duration (≥6 months versus < 6 months) and overweight or obesity as compared to underweight or normal weight, in total (odds ratio 1.46, 95% confidence interval 0.69–3.08) or in boys and girls separately. Conclusions We found no association between breastfeeding duration and childhood and adolescence BMI up to 16 years of age or the development of overweight or obesity.